The Feasibility of Development of Multi Split Model Based Hands On-Mind on Approach as Reconstruction Basic Literature and Character Value - Lily Thamrin; Dyoty Aulia Vilda Ghasya; Rio Pranata (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine the feasibility of developing a multi-split model based on a hands on-mind on approach in elementary schools. The research method used is a mixed method, combining quantitative and qualitative methods in a series of studies. This research also uses RD (Research and Development), the Four-D development or 4-D models. The data source in this study was obtained from the results of the validation of the feasibility of developing a multi-split model based on a hands on-mind on approach which two experts in their fields validated. Product development in the form of a learning model, "Multi Split Model Based on Hands On-Mind On Approach" is valid or feasible. Validation was conducted to see the content validity, construct validity, and revision of the learning model. The results of the validation analysis of the feasibility of the development carried out show that the average content validity value of 4.06 is in the valid category, and the construct validity of 4.20 is in the "valid" category with a statement that it can be used with minor revisions. At the same time, the revision of the learning model is based on the value of content and construct validity and suggestions from validators. Based on the validation results, the feasibility level of developing a multi-split model based on a hands on-mind on approach is very good and suitable for use.